Association of ultrasound‐based measures of fetal body composition with newborn adiposity. (29th November 2016) - Ikenoue, S.; Waffarn, F.; Sumiyoshi, K.; Ohashi, M.; Ikenoue, C.; Buss, C.; Gillen, D. L.; Simhan, H. N.; Entringer, S.; Wadhwa, P. D.
Summary: Background: Newborns exhibit substantial variation in gestational age‐adjusted and sex‐adjusted fat mass proportion. The antecedent characteristics of fetal body composition that are associated with newborn fat mass proportion are poorly understood. Objective: The aim of this study was to determine whether a composite measure of fetal fat mass is prospectively associated with newborn adiposity. Methods: In a longitudinal study of 109 low‐risk pregnancies, fetal ultrasonography was performed at approximately 12, 20 and 30 weeks gestation. Estimated fetal adiposity (EFA) was derived by integrating cross‐sectional arm and thigh per cent fat area and anterior abdominal wall thickness. Newborn per cent body fat was quantified by Dual Energy X‐Ray Absorptiometry. The association between EFA and newborn per cent body fat was determined by multiple linear regression. Results: After controlling for confounding factors, EFA at 30 weeks was significantly associated with newborn per cent body fat (standardized β  = 0.41, p  < 0.001) and explained 24.0% of its variance, which was substantially higher than that explained by estimated fetal weight (8.1%). The observed effect was driven primarily by arm per cent fat area. Conclusions: A composite measure of fetal adiposity at 30 weeks gestation may constitute a better predictor of newborn per cent body fat than estimated fetal weight by conventional fetal biometry. Fetal arm fat deposition may represent an early indicator of newborn adiposity. After replication, these findings may provide a basis for an improved understanding of the ontogeny of fetal fat deposition, thereby contributing to a better understanding of its intrauterine determinants and the development of potential interventions.